ANALISIS KESALAHAN DALAM MEMECAHKAN MASALAH FUNGSI KUADRAT BERDASARKAN LANGKAH POLYA - Nandita Ayunengdyah; Siti Khabibah; Sari Saraswati (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2020)
Problem solving becomes something important to be taught to students because it can practice critical thinking in solving the problems related to daily life. One of the mathematical materials that important to be taught because it related to daily life is the quadratic function. In fact, students still have many mistake to solve the problem of quadratic function problem that oriented to problem solving. The aim of this research is to describe (1) the student error location of problem solving based on Polya's step in the quadratic function material for tenth grade, (2) the student error causes of problem solving based on Polya's step in the quadratic function material for tenth grade. This research is a qualitative descriptive research. The subjects in this research were 24 students of tenth grade in MA Al Anwar Pacul Gowang Jombang. Data collection techniques are the test, interview, and documentation. Data analysis through the data reduction, data presentation, and data verification. The results show that the location of the error problem solving made by students was the second Polya's step (making plan) and fourth (looking back). The causes of student problem solving error is because students are not accustomed to do on story problem, so that students are not understand the problem and rushing in working it.